Geological evaluation of black shale as a suitable Supplementary Cementitious Material (SCM) to optimize the use of clinker in cement production - Nunoo, S.; Owusu-Sasu, T.A.; Amponsah, P. O.; et al. (Heliyon, 2024)
Faced with challenges like resource depletion and climate change, the cement industry needs sustainable solutions. This study explores the potential of geologically-delinaeated black shale from Apersua, Ghana, as a supplementary cementitious material (SCM) to reduce reliance on traditional methods. The researchers analysed the shale’s chemical composition and mineralogy, then created laboratory cement formulations with varying black shale content. These were compared to standard formulations without shale. The results show cement with black shale has comparable compressive strength, meeting standard requirements. Even a formulation with only black shale (excluding limestone, a common ingredient) passed strength tests. Overall, the black shale demonstrated good potential as a SCM based on strength, chemical makeup, setting time, and its possible contribution to durability. This research suggests that black shales from Apersua are worth exploring further as a sustainable and potentially cost-effective alternative in cement production.
Research Article
Keywords: Black shales; Cement; Supplementary cementitious material